Technology and mental health a clinician's guide to improving outcomes - Reger, Greg M. (New York, NY ; Abingdon, Oxon : Routledge, Taylor & Francis Group, 2021)
Technology and Mental Health provides mental health clinicians with expert, practical, clinical advice on the questions and considerations associated with the adoption of mental health technology tools in the computer age. Increasingly, clinicians want to use technology to provide clients support through smartphones and mobile applications or to reach clients in remote or rural areas. However, using these tools in practice raises many practical and ethical questions. The book explains current technological developments in therapy, including mobile apps, telemental health, andvirtual reality programs. Each chapter gives real-world guidance on adopting and using technology interventions, and the book spans a wide range of populations. Providers are introduced to the evidence supporting various technology-based interventions and areas for future development. Combining theory, research, and case studies, this practical guide teaches clinicians how to integrate technology into therapeutic interventions with clients.
OCLC-licensed vendor bibliographic record.
Keywords: Mental health services -- Technological innovations; Psychotherapy -- Technological innovations; Mental health -- Technological innovations; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health